2014
DOI: 10.1111/jomf.12107
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Hostility and Maternal Hostility in European American and African American Families

Abstract: The authors examined the hypothesized influence of maternal and paternal hostility on youth delinquency over time. The investigation addressed significant gaps in earlier research on parental hostility, including the neglect of father effects, especially in African American families. Using prospective, longitudinal data from community samples of European American (n = 422) and African American (n = 272) 2-parent families, the authors examined the independent effects of paternal and maternal hostility on youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Other studies find support for the protective role of maternal sensitivity or positive parenting and child self‐esteem (for victimization) and prosocial friends (for perpetration; e.g., Garrido & Taussig, ). Wu et al () found paternal hostility (including physical acts) directed at youth predicted relative increases in delinquency over time in both African American and White families, but only for paternal not maternal hostility (even though frequency of maternal hostility was higher).…”
Section: Individual and Relational Contextsmentioning
confidence: 99%
“…Other studies find support for the protective role of maternal sensitivity or positive parenting and child self‐esteem (for victimization) and prosocial friends (for perpetration; e.g., Garrido & Taussig, ). Wu et al () found paternal hostility (including physical acts) directed at youth predicted relative increases in delinquency over time in both African American and White families, but only for paternal not maternal hostility (even though frequency of maternal hostility was higher).…”
Section: Individual and Relational Contextsmentioning
confidence: 99%
“…Parental hostility was the only significant predictor for children’s bullying in 52 parent/caregivers studied in an evaluation of a program to reduce early childhood bullying (Burkhart, Knox, & Brockmyer, 2013). Paternal hostility, in particular, significantly predicted relative increases in youth delinquent behaviors (Wu et al, 2014). Also, maternal hostility has been found to predict disruptive behavior in children and is defined as “maternal anger, criticism, negativity and disapproval directed towards the child” (Sellers et al, 2014, p. 112).…”
Section: Themesmentioning
confidence: 99%